ANALISIS PENGARUH INFRASTRUKTUR TERHADAP KEMANDIRIAN DESA(STUDI DI PEDESAAN KABUPATEN KEDIRI) - Wulansari, Rizqiana Devi (Jurnal Ilmiah Mahasiswa FEB, 2020)
nfrastructure has an important role in economic development efforts, infrastructure can support the development of economic activity in a region, so that infrastructure development can improve the regional economy. The availability of adequate infrastructure cannot be separated from the influence of the village government. Decentralization has made the concept that development must be directed at the lowest level of the government structure, namely the village. The village as the lowest administrative area has independently been used as the subject of development, to reducing the gap in rural and urban development which tends to be urban biased.The village is an autonomous region and has the privilege of managing finances, allocating village funds, electing village heads and the development process. The purpose of this study was to determine whether there was an effect of the availability of infrastructure (irrigation, health facilities, educational facilities, village markets and commercial tourism) on village independence, using secondary data obtained through the 2018 PODES survey using logistic regression analysis.The results showed thatthe irrigation and village market variables showed significant positive results on village independence. Therefore, one of the efforts to increase village independence can be done by increasing irrigation access and village markets.Keywords: Rural, Infrastructure, and PADesa